SIARAN RADIO CITRA 99.4 FM SEBAGAI MEDIA PELESTARIAN TEMBANG SUNDA BAGI SISWA SEKOLAH DASAR - Sofian, Maylan (Mimbar Sekolah Dasar, 2015)
This research inspects about preservation of traditional art through tembang sunda cianjuran on Citra radio 99, 4 FM Sumedang. The problems inspected in this research as follows, First, how does the preservation of tembang sunda cianjuran present on the Citra Radio 99, 4 FM broadcast program? Second, how does the contribution of the electronic media Citra radio broadcast programme for tembang sunda cianjuran and the artist in Sumedang? In order to get the answer to the problems, the qualitative research done, that is the content analysis. Content analysis is one of the research methods to produce objective and systematic description. The result from this research shows that Citra Radio 99, 4 FM Sumedang broadcast program can be a system support to tembang sunda cianjuran. This broadcast can stimulate the listener memory about tembang sunda cianjuran that the listener ever heard or studied when they are still young. The contribution of the radio can be felt by the artist, especially to the popularity of the music player and the singer of Citra radio 99,4 FM.Keywords: tembang, preservation, media.